Proceedings. IEEE International Conference on Multimedia and Expo
DOI: 10.1109/icme.2002.1035901
|View full text |Cite
|
Sign up to set email alerts
|

Watershed parallel algorithm for asynchronous processors array

Abstract: ISBN: 0780373049A joint algorithm-architecture analysis leads to a new version of picture segmentation system adapted to multimedia mobile terminal constraints. The asynchronous processors network, with a granularity level of one processor per pixel, based on data flow model, takes less than 10 mu s to segment a SQCIF $88*72 pixels - image (about 2000 times faster than the classical sequential watershed algorithms). The main originality of the proposed algorithm is only one global synchronization point is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…It is shown that the actual flooding is accomplished by a single instruction in a wavepropagating manner. The achieved results are comparable to application specific arrays [6,11] In general, we can see that an appropriate decomposition of complex algorithms into simple operations can provide a significant performance increase when implemented on the proposed architecture.…”
Section: Watershed Transformsupporting
confidence: 53%
“…It is shown that the actual flooding is accomplished by a single instruction in a wavepropagating manner. The achieved results are comparable to application specific arrays [6,11] In general, we can see that an appropriate decomposition of complex algorithms into simple operations can provide a significant performance increase when implemented on the proposed architecture.…”
Section: Watershed Transformsupporting
confidence: 53%
“…[14], due to known optimizations applied to the sequential algorithm and corrections done on the parallel one. In a fine grain configuration, our system is able to segment about 60,000 QCIF images per second, that is to say a speedup factor close to 10,000.…”
Section: Complexity Estimationmentioning
confidence: 99%
“…A description of this asynchronous version of the "HillClimbing" algorithm was previously presented in [14], and will be detailed in Section 2. This paper then focuses on the formal proof of the algorithm correctness (Section 3).…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms were proposed [13,14]. They consider a topographical representation of the image, where the altitude is given by the grey level of each pixel.…”
Section: Watershed Segmentationmentioning
confidence: 99%